Long-Term Follow-Up of Chinese Herbal Medicines Combined with Conventional Treatment in Patients with Acute Coronary Syndrome after Percutaneous Coronary Intervention： A Multicenter Randomized Controlled Trial - Wang, Pei-li; Zhang, Lei; Wang, Shao-li; Yang, Qiao-ning; Gao, Zhu-ye; Du, Jian-peng; Zhang, Da-wu; Fu, Chang-geng; Gu, Feng; Xu, Hao; Li, Li-zhi; Wang, Cheng-long; et al. (Chinese journal of integrative medicine, 2017)
Objective： To evaluate the prognosis effect of Chinese herbal medicines（CHMs） for benefiting qi and activating blood circulation adjunctive to conventional treatment in patients with acute coronary syndrome（ACS） after percutaneous coronary intervention（PCI）. Methods： A total of 702 patients with ACS who underwent PCI were enrolled and randomly assigned to receive conventional treatment plus CHMs for benefiting qi and activating blood circulation（treatment group, 351 cases） or conventional treatment alone（control group, 351 cases） for 6 months. Six months later, all patients received conventional treatment alone. Follow-ups were scheduled at 6th, 12 th, 18 th, 24 th month after enrollment in April 2008, and the final follow-up visit was during September 2011 and November 2011. The primary endpoint was the composite of cardiac death, nonfatal myocardial infarction or revascularization（PCI or coronary artery bypass grafting）; and the secondary endpoint was the composite of re-admission for ACS, congestive heart failure, nonfatal stroke or other thrombus events. Results： A total of 621（88.59%） patients completed 35.4±3.8 months follow-up, while 80（11.41%） patients withdrew from the trial（41 in the treatment group and 39 in the control group）. The incidence of primary endpoint was 5.7%（20 patients） in the treatment group versus 10.86%（38 patients） in the control group [relative risk（RR）： 0.53; 95% confidence interval（CI）： 0.30, 0.88; P=0.013; absolute risk reduction（ARR）： –0.052, 95% CI： –0.06, 0.01]. The incidence of secondary endpoint was 5.98%（21 patients） in the treatment group versus 10.28%（36 patients） in control group（RR： 0.58, 95% CI： 0.33, 0.97, P=0.037; ARR： –0.043, 95% CI： 0.06, 0.01）. Most of the primary and secondary endpoints were occurred in 18 months（84.50% in the treatment group versus 78.10% in the control group）. Conclusion： CHMs for benefiting qi and activating blood circulation adjunctive to conventional treatment improved clinical outcomes for patients with ACS after PCI in long-term follow-up.